Do world shocks drive domestic business cycles? Some evidence from structural estimation - Thomas Lubik; Wing Leong Teo (The Johns Hopkins University, Department of Economics, 2005)
Existing results on the contribution of terms of trade and world interest rate shocks to output fluctuations in small open economies range from less than 10% to almost 90%. We argue that an identification problems lies at the heart of these vastly dierent results. In this paper, we overcome this by estimating a DSGE model using a structural Bayesian estimation approach. We apply our methodology to five developed and developing economies.. Our approach allows us to e?ciently exploit cross-equation restrictions implied by the structural model. We find that world interest rate shocks are the main driving forces of business cycles in small open economies while terms of trade shocks are not.
Keywords: C32; F41; 330; World Shocks; Business Cycles; Small Open Economy Model; Structural Estimation; Bayesian Analysis; Konjunkturzusammenhang; Schock; Kleines-offenes-Land; Dynamisches Gleichgewicht; Terms of Trade; Schätzung; Australien; Kanada; Neuseeland; Mexiko; Chile